Aiming High : Navigating the Next Stage of Malaysia’s Development - World Bank (World Bank, Washington, DC, 2021)
Malaysia is likely to make the transition from an upper-middle-income economy to a high-income economy within the next five years, despite thesetback of the COVID-19-induced recession in 2020. This transition represents an important milestone in Malaysia’s development, having transformed living standards in less than a generation, slashing the extreme poverty rate to less than one percent of the population, and ending the country’s long tenure in the “middle-income trap”. However, Malaysia has been severely affected by COVID-19 and it will take several years beforethe scars of the pandemic are fully erased. The country experienced a “triple shock”: the direct health impact of the virus; the economic impact of movement restrictions; and the growth impact of a global recession. With Malaysia on the verge of achieving this transition, it is an opportune time to address a number of questions regarding the speed of Malaysia’s growth, its quality, and its sustainability. Malaysia is growing slower thanmany countries that achieved high-income status in recent decades. In addition, compared to many other countries that have graduated from middle-income status, it has a lower share of employment at high skill levels and higher levels of inequality. And, compared to countries in the OECD, Malaysia collects less in taxes, spends less on social protection, and performs relatively poorly in terms of measures related to environmentalmanagement and the control of corruption. Many of these fault lines have become exposed during the pandemic. Most significantly, there is a growing sense that despite economic growth, the aspirations of Malaysia’s middle-class are not being met and that the economy hasn’t produced enough well-paying, high-quality jobs. There is a widespread sense that the proceeds of growth have not been equitably shared and that increases in the cost-of-living are outstripping incomes, especially in urban areas, where three-fourths of Malaysians reside. Policies and institutions that have worked in the past may no longer be appropriate for the next stage of Malaysia’s development, with a different set of policies and institutions required at higher levels of income and development. The policies that enabled Malaysia to successfully make the transition from low- to middle-income need to be adapted to meet the challenges it will face in the future. At an earlier stage of its development, factor accumulation was a key driver of Malaysia’s growth. As it makes the transition, it will increasingly need to depend upon more knowledge-intensive and productivity-driven growth, closer to the technological frontier and with a greater emphasis on achieving inclusive and sustainable development. As Malaysia positions itself for the next phase of its development and beyond the pandemic, many of the issues related to this transformation are being addressed and discussed, including through the 12th Malaysia Plan and the Shared Prosperity Vision 2030. With the impact of the COVID-19 pandemic and its potential to depress growth into the future, issues related to Malaysia’s readiness for the future have become even more significant. The analysis in this report suggests that for Malaysia to fulfil its potential, to transition successfully to high-income and developed country status, and to sustain equitable growth beyond that point, reforms are needed in six broad and inter-linked areas: (i) revitalizing long-term growth; (ii) boosting competitiveness; (iii) creating jobs; (iv) modernizing institutions; (v) promoting inclusion; and (vi) financing shared prosperity.